Kina powiatu jaworskiego lat 1963–1973 w liczbach — przykład wykorzystania dokumentacji statystycznej - Ivo Łaborewicz (Studia Filmoznawcze)
The aim of the article is to show the possibility of using statistical forms in the study of the history of cinemas. The files of the Jawor District Statistical Inspectorate (1962–1975) were used. Statistical reports were analysed, tabulating data at the level of the entire district and individual cinemas. This made it possible to characterise the changes occurring in the number of cinemas, audience size, number of screenings, attendance, and income. Particularly valuable were the forms for individual venues, containing additional information for local cinemas such as their names, addresses, names of managers, and others. These types of individual sources have not yet been subject to research analysis.